Analysis and Linguistic Perspective of the Traditional Bungong Jeumpa Song - Saputri, Maya; Yusma Idris (Enigma in Cultural, 2023)
By analyzing the metaphors included in the song "Bungong Jeumpa," we can deduce that this composition is an artistic masterpiece that abounds in symbolism and cultural significance. Each aspect inside the song lyrics, beginning with "Bungong Jeumpa," representing the allure of ladies, and extending to "Jeumpa Beach," portraying the splendor of nature, encompasses profound insights into Acehnese culture. This song exemplifies how the art of music can serve as a potent tool for commemorating and portraying the splendor of nature, mundane existence, and human emotions. Within the framework of this song, "Bungong Jeumpa" encompasses not only musical elements but also serves as a profound cultural introspection with significant implications. The utilization of diverse metaphors in song lyrics exemplifies the ability of the cultural arts to articulate cultural values, human emotions, and profound perspectives on the world. This song unequivocally demonstrates how the art of music serves as a medium for commemorating nature, mundane existence, and emotions within a vibrant and exquisite culture.